Clinicopathological profile, risk factors and outcome of adult biopsy-proven infection-related glomerulonephritis: A single centre prospective study - Ayesha Aziz; Abdul Wajid (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the clinicopathological profile, risk factors and outcomes of biopsy-proven infection-related glomerulonephritis. Method: The prospective, cross-sectional, observational study was conducted at the Department of Nephrology, Ayub Teaching Hospital, Abbottabad, Pakistan, from April 5, 2023, to December 30, 2024, and comprised patients of either gender aged at least 18 years who underwent renal biopsy. Demographic, clinical, laboratory and histopathological data was collected prospectively. Outcomes were tracked, and comorbidities and histological features were assessed for prognostic relevance. Data was analysed using SPSS 23. Results: Of the 180 renal biopsies, 22(12.2%) were diagnosed with biopsy-proven infection-related glomerulonephritis; 14(63.6%) males and 8(36.4%) females, with overall mean age being 36.23±19.79 years. Renal dysfunction was evident with elevated serum creatinine 3.30±3.11mg/dL and hypoalbuminaemia 3.19±0.6mg/dl accompanied by nephrotic-range proteinuria 3.82±3.05g/day. Haematuria 17(77.2%) and leucocyturia 12(54.5%) were the most common presentations. Elevated antistreptolysin O titers were found in 9(41%) cases, and hypocomplementaemia in 13(59%). Histopathology revealed neutrophilic infiltration 19(86.6%), endocapillary proliferation 18(81.8%), mesangial proliferation 17(77.2%), and crescents 5(22.2%), with interstitial fibrosis 6(27.2%) signalling chronicity. Immunofluorescence showed dominant complement component 3 deposits 22(100%) alongside immunoglobulins G, M and A co-deposits. Hypertension 8(36.4%) was a key comorbidity, alongside diabetes 2(9.1%) and anaemia 5(22.7%). While 18(81.8%) patients achieved full recovery, 2(9.1%) progressed to chronic kidney disease and 2(9.1%) to end-stage renal disease. Conclusion: Infection-related glomerulonephritis in adult patients was found to present with diverse clinicopathological features, often post-infection. Most patients recovered, but progression to chronic kidney disease and end-stage renal disease correlated with hypertension and chronic histological changes. Key Words: Glomerulonephritis, Infection, Kidney diseases, Biopsy, Risk factors.